1991
DOI: 10.1056/nejm199109263251303
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Antepartum Maternal Metabolism and Intelligence of Offspring

Abstract: Maternal diabetes during pregnancy may affect behavioral and intellectual development in the offspring. The associations between gestational ketonemia in the mother and a lower IQ in the child warrant continued efforts to avoid ketoacidosis and accelerated starvation in all pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
197
2
15

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(221 citation statements)
references
References 15 publications
7
197
2
15
Order By: Relevance
“…This paper finds that the strongest (and statistically significant) effects on math test scores are in the first trimester, when siblings fixed effects are used. This is also consistent with the findings of Rizzo et al (1991), who ascribe low blood glucose levels as a mechanism through which cognitive functioning is impaired in the first trimester. The effects on Raven's CPM, though statistically insignificant for all trimesters, are strongest for the third, followed by the first, trimester.…”
Section: A Interpreting Effects By Trimester For Salient Outcomessupporting
confidence: 80%
See 1 more Smart Citation
“…This paper finds that the strongest (and statistically significant) effects on math test scores are in the first trimester, when siblings fixed effects are used. This is also consistent with the findings of Rizzo et al (1991), who ascribe low blood glucose levels as a mechanism through which cognitive functioning is impaired in the first trimester. The effects on Raven's CPM, though statistically insignificant for all trimesters, are strongest for the third, followed by the first, trimester.…”
Section: A Interpreting Effects By Trimester For Salient Outcomessupporting
confidence: 80%
“…Both studies emphasized the necessity for pregnant women to eat during the daytime. Thereafter, several studies have shown that accelerated starvation caused by fasting during pregnancy is correlated with the malfunctioning of certain cognitive functions (Rizzo et al, 1991).…”
Section: Evidence On First Stage Effectsmentioning
confidence: 99%
“…Esses resultados sugerem que doenças que levam à macrosomia fetal, como a diabetes gestacional 42,43 , poderiam influenciar o desenvolvimento de problemas de saúde mental em etapas posteriores. Alguns estudos têm evidenciado associação entre diabetes gestacional e transtornos de comportamento, menor capacidade cognitiva e maior hospitalização por transtornos no neuro-desenvolvimento em crianças de mulheres com esta doença 44,45 .…”
Section: Discussionunclassified
“…Moreover, insulin-like growth factor has a neuroprotective anti-apoptotic effect (Rizzo et al, 1991) and down regulation of expression of insulin-like growth factor and its receptor in diabetes might also be expected to lead to neuronal loss (Li et al, 2002;Russell & Feldman, 1999).…”
Section: Discussionmentioning
confidence: 99%